Interface strain in vertically stacked two-dimensional heterostructured carbon-MoS2 nanosheets controls electrochemical reactivity - Landon Oakes (Nature Portfolio, 2016)
Two-dimensional materials are promising for electrochemical energy storage, conversion, catalysis, and sensing. Here the authors leverage strain engineering using a two-dimensional stacked carbon-MoS2 material to control chemical storage pathways in MoS2upon lithium metal insertion.